2012
DOI: 10.1097/gco.0b013e328355854d
|View full text |Cite
|
Sign up to set email alerts
|

Array comparative genomic hybridization

Abstract: Although clinical results have been promising, further evidence is required to establish whether PGS results in enhanced live birth rate, and if this is the case, to identify which patients may benefit from the procedure. The results from several ongoing randomized controlled trials, performed at different cell biopsy stage and categories of patients, will provide the data needed to accept or reject the clinical efficacy of PGS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The risk of misdiagnosis of chromosomal mosaicism is reduced by the analysis of several cells obtained by TE biopsy (5–10), and it has been demonstrated that most mosaic blastocysts do not contain any normal cells [62]. Clinical data suggest that an approach combining blastocyst biopsy and comprehensive chromosome screening using array CGH or microarray CGH may represent the optimal approach for preimplantation genetic screening [15, 52]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of misdiagnosis of chromosomal mosaicism is reduced by the analysis of several cells obtained by TE biopsy (5–10), and it has been demonstrated that most mosaic blastocysts do not contain any normal cells [62]. Clinical data suggest that an approach combining blastocyst biopsy and comprehensive chromosome screening using array CGH or microarray CGH may represent the optimal approach for preimplantation genetic screening [15, 52]. …”
Section: Discussionmentioning
confidence: 99%
“…Embryo implantation and live birth rates are not increased after transfer of embryos screened by FISH-based PGS, probably because the limited number of analyzed chromosomes is not sufficient [14, 15]. In fact, it has been demonstrated that aneuploidies may occur in preimplantation embryos in any of the 23 chromosomes indicating that aneuploidy screening of all chromosomes is necessary to determine whether an embryo is chromosomally normal [1619].…”
Section: Introductionmentioning
confidence: 99%